Grape aroma precursors in cv. Nebbiolo as affected by vine microclimate. (15th November 2016) - Asproudi, Andriani; Petrozziello, Maurizio; Cavalletto, Silvia; Guidoni, Silvia
Highlights: Microclimates influence on aroma precursors in Nebbiolo grapes was investigated. Norisoprenoid precursors accumulate from pre-veraison until 3 weeks post-veraison. Vine vigour and vineyard aspect affects norisoprenoids seasonal trend. Low light in the vigorous vines penalized norisoprenoids peak. Extremely high temperature caused a decline of aroma precursors at harvest. Abstract: The influence exerted by bunch microclimate on some C13 -norisoprenoid precursors content was investigated for the first time in Nebbiolo grapes during ripening. Samples were collected, during two consecutive seasons, from two vineyards, which are characterized by different microclimatic conditions caused by vine vigour heterogeneity and different vineyard aspects. Enzymatic hydrolysis of the glycosides extracted from the grapes, and subsequent GC–MS determination of the aglycones, highlighted that the majority of norisoprenoid glycosides accumulated in Nebbiolo berries from pre-veraison until 3–4 weeks post-veraison. Vineyard aspect and vine vigour affected the timing of the maximum concentration of norisoprenoid precursors and their subsequent decrease at harvest. Low light in the vigorous blocks penalized norisoprenoids peak concentration. In the south less vigorous blocks, a decline of total norisoprenoids content during the pre-harvest period was observed. This decline appeared mainly regulated by the temperature. Vintage and/or microclimatic conditions affected the final content of some important norisoprenoids.